2016
DOI: 10.1111/jbl.12112
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Global Inventory Prepositioning Locations in Humanitarian Operations—A Delphi Study

Abstract: T his article investigates the factors that are important to humanitarian organizations when determining locations for inventory prepositioning in preparation for emergencies-a critical decision faced by humanitarian managers. Current research in the sector is rich with mathematical models that focus on this decision, although these models have a limited scope in terms of decision factors. Through a Delphi study our article investigates, identifies, and orders a comprehensive set of factors that decision maker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 52 publications
3
34
0
1
Order By: Relevance
“…Humanitarian organizations must overcome many challenges to dispatch suitable relief materials with agility (Van Wassenhove 2006; Kovács and Spens 2007;Duran et al 2013). As part of an effort to effectively manage these challenges, there is a growing operational focus on pre-positioning logistics (Barbarosoglu and Arda 2004; Özdamar et al 2004;Yi and Özdamar 2007;Özdamar and Ertem 2015;Ahmadi et al 2015;Victoria et al 2015;Chen et al 2017) and inventory management (Beamon and Kotleba 2006;Davis et al 2013;He and Zhuang 2016;Richardson et al 2016). These studies are essential for identifying the most effective and efficient relief management strategies for a set of circumstances (Van Wassenhove 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Humanitarian organizations must overcome many challenges to dispatch suitable relief materials with agility (Van Wassenhove 2006; Kovács and Spens 2007;Duran et al 2013). As part of an effort to effectively manage these challenges, there is a growing operational focus on pre-positioning logistics (Barbarosoglu and Arda 2004; Özdamar et al 2004;Yi and Özdamar 2007;Özdamar and Ertem 2015;Ahmadi et al 2015;Victoria et al 2015;Chen et al 2017) and inventory management (Beamon and Kotleba 2006;Davis et al 2013;He and Zhuang 2016;Richardson et al 2016). These studies are essential for identifying the most effective and efficient relief management strategies for a set of circumstances (Van Wassenhove 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These are highlighted by several authors identified through a literature reviews on humanitarian aid management. The factors are information (van der Laan et al, 2016;Yilmaz & Kabak, 2016), communication (Madianou et al, 2015;Martin et al, 2016), collaboration (Martin et al, 2016;Nagurney et al, 2016), coordination (Martin et al, 2016;Richardson et al, 2016) and cooperation (Joshi & Nishimura, 2016;Martin et al, 2016). These are the key success factors for disaster management stakeholders in managing the humanitarian aid distribution process efficiently and effectively.…”
Section: Humanitarian Aidmentioning
confidence: 99%
“…Shaikh and Khoja (2014) suggested that the consensus level is one of the fundamental elements in Delphi studies, and a sufficiently high consensus level should be utilised as a benchmark for retaining the factors that are preferred by participants in the first round. However, as there is no fixed measure to define the consensus level (Becuwe et al, 2017), variable statistics were used for consideration of the consensus level as suggested by various studies (Richardson, de Leeuw, & Dullaert, 2016;Gracht, 2012;Harmsen et al, 2015;Tharisara, Kanchana, & Turner, 2016;Williams, 2016;Hasson, Keeney, & McKenna, 2000;Hsu and Sandford,2007). Following (Bulger & Housner, 2007;Green, Jones, Hughes, & Williams, 1999;Lohuis, van Vuuren, & Bohlmeijer, 2014;Neuer Colburn, Grothaus, Hays, & Milliken, 2016), this study uses a consensus level of four for five-point Likert scale questions.…”
Section: Demographics Of Participantsmentioning
confidence: 99%